Motor engineering knowledge for marine engineers - Russell, Paul A. (Paul Anthony); Morton, Thomas D. (Thomas Dunn) 1929-; Jackson, Leslie 1929-; Prince, Anthony S. (Reeds marine engineering and technology, 2013)
This is a specific examination guide based on the syllabuses of Motor Engineering Knowledge for Class 2 and Class 1 Marine Engineer Motor Certificates and Motor Endorsements. There is also a selection of questions of the type set in the exams for First and Second Class Engineers.